Cultural Involvement in Information Policy Implementation in Indonesia: Growth Articles and Possible Future Research - Rahmayanti, Rahmayanti; Khumayah, Siti (Jurnal Polisci, 2024)
Government performance alone does not produce information policy; cultural involvement plays a major role in meeting people's information demands. It's useful to understand more about the evolution of cultural involvement in Indonesian information policy implementation, regardless of the quantity and diversity of publications. Studying the key components of cultural participation in the literature on information policy requires a thorough bibliometric investigation. The purpose of this study is to look into patterns of growth and pinpoint areas for future research that other scholars might want to take up. In order to further define the research objectives, the methodology utilized through Scopus is extended to include VOSviewer data processing. According to the findings, there is a tendency for the number of publications on this subject to rise between 2013 and 2022. This suggests that there may be more study possibilities in the future to examine Indonesia's public information regulations' transparency.